Development of the skull and pectoral girdle in Siberian sturgeon, Acipenser baerii, and Russian sturgeon, Acipenser gueldenstaedtii (Acipenseriformes: Acipenseridae). (7th February 2017) - Warth, Peter; Hilton, Eric J.; Naumann, Benjamin; Olsson, Lennart; Konstantinidis, Peter
Abstract: The head is considered the major novelty of the vertebrates and directly linked to their evolutionary success. Its form and development as well as its function, for example in feeding, is of major interest for evolutionary biologists. In this study, we describe the skeletal development of the cranium and pectoral girdle in Siberian ( Acipenser baerii ) and Russian sturgeon ( A. gueldenstaedtii ), two species that are commonly farmed in aquaculture and increasingly important in developmental studies. This study comprises the development of the neuro‐, viscero‐ and dermatocranium and the dermal and chondral components of the pectoral girdle, from first condensation of chondrocytes in prehatchlings to the early juvenile stage and reveals a clear pattern in formation. The otic capsules, the parachordal cartilages, and the trabeculae cranii are the first centers of chondrification, at 8.4mm TL. These are followed by the mandibular, then the hyoid, and later the branchial arches. Teeth form early on the dentary, dermopalatine, and palatopterygoid, and then appear later in the buccal cavity as dorsal and ventral toothplates. With ongoing chondrification in the neurocranium a capsule around the brain and a strong rostrum are formed. Dermal ossifications start to form before closure of the dorsal neurocranial fenestrae. Perichondral ossification of cartilage bones occurs much later in ontogeny. Our results contribute data bearing on the homology of elements such as the lateral rostral canal bone that we regard homologous to the antorbital of other actinopterygians based on its sequence of formation, position and form. We further raise doubts on the homology of the posterior ceratobranchial among Actinopteri based on the formation of the hyoid arch elements. We also investigate the basibranchials and the closely associated unidentified gill‐arch elements and show that they are not homologous. J. Morphol. 278:418–442, 2017. © 2017 Wiley Periodicals, Inc.